An Assessment of the stress level of special education teachers in Jose Fabella memorial school Mandaluyong City - Villamin, Geraldine E. (Manila : National University, 2009)
This research deals with the stress among SPED teachers of Jose Fabella Memorial School, cause of their stress, the signs and symptoms and the coping strategies to overcome this psychological factors.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.